The power of grit on lecturer’s job satisfaction through affective commitment - Irvandi Gustari; Widodo Widodo (Jurnal Konseling dan Pendidikan, 2021)
This study explores the empirical effect of grit on job satisfaction mediating by affective commitment. This research uses a quantitative approach to the survey method through a Likert scale model questionnaire. The research participants are 230 lecturers in Indonesia selected by accidental sampling. Data analysis uses path analysis supported by descriptive statistics and correlational matrics. The research result indicates that grit significantly affects job satisfaction, directly and indirectly, mediating by affective commitment. Thus, the lecturer’s job satisfaction can improve through grit and affective commitment. A new model about the effect of grit on job satisfaction mediating by affective commitment was confirmed. Therefore, researchers and practitioners can adopt a new empirical model to increase job satisfaction through grit and affective commitment in the future.